Highhydrostatic pressure as a tool to improve the antioxidant activity of watercress extracts - Pinela, José (2022)
Watercress (Nasturtium officinale R. Br.) belongs to the Brassicaceae family together with broccoli, cabbage, mustard and Brussels sprouts. This semiaquatic plant is source of bioactive phytochemicals such as polyphenols, glucosinolates, and carotenoids, which have received great importance due to their several health benefits linked to antioxidant activity [1,2]. To obtain plant extracts, the extraction method must be thought out carefully to ensure successful recovery of the bioactive compounds. Therefore, the selection of an appropriate extraction method is important for the production of high quality antioxidant extracts, otherwise the extraction can lead to degradation of the target compounds. High pressure processing (HPP) has been used in the extraction of bioactive molecules from plant matrices with very promising results because, since no heat is used, it avoids harmful effects on thermosensitive compounds and, consequently, preserves better their biological activities. HPP provides higher extraction yields and selectivity for target compounds than conventional extraction methods [3]. Pressure can disrupt plant tissues and enhance mass transfer of solvent into the materials and the soluble constituents into the solvent. Thus, this study was carried out to outline the best extraction conditions to obtain antioxidant extracts from watercress. Powdered watercress was processed according to a central composite design of 20 runs, in which five levels of time (1.5–33.5 min), pressure (0.1–600 MPa) and ethanol concentration (0–100%, v/v) were combined. The antioxidant activity of the obtained extracts was measured in vitro by the DPPH• scavenging activity and reducing power assays, and the results were presented as EC50 values and used as response variables in the optimization by response surface methodology. Design Expert software was used for regression and graphical analysis of the data. A quartic polynomial equation that correlates the response as a function of the independent variables and their interaction was developed. The models were successfully fitted to the experimental data, statistically validated based on high F-values (>64.9) and R2adj (>0.96), and used to navigate the design space and predict the optimal extraction conditions. Considering both response criteria, the HHP conditions that sustainably maximized the extract antioxidant activity required a low processing time (1.5 min) and an intermediate pressure (319 MPa) and solvent concentration (55% ethanol, v/v), and yielded EC50 values of 0.45 mg/mL and 0,41 mg/mL for the DPPH and reducing power assays, respectively. HHP extraction revealed so to be a time-saving process comparatively with conventional methods.